SOCIAL ECONOMIC LAW IN THE DIGITAL ERA: A REVIEW OF THE LITERATURE AND ITS FUTURE IMPLICATIONS - Loso Judijanto; Iyad Abdallah Al- Shreifeen; Hadenan Towpek (CV. Adiba Aisha Amira, 2024)
In today's digital era, social economic law is undergoing a significant shift due to the technological revolution that affects all aspects of people's lives. This study aims to review relevant literature to identify how social economic law is adapting to the changes brought about by the digital era and its future implications. The research is conducted through a comprehensive literature review on the concept of social economic law, the impact of digitalisation, and the challenges and opportunities arising from the interaction between the two. The results of this study show that digital technologies, such as artificial intelligence and blockchain, offer opportunities to improve efficiency and transparency in the social economy, but also introduce risks related to data security, privacy, and access gaps. The study concludes that inclusive and responsive policy adaptations from stakeholders are needed to ensure that social economy law can support equitable and sustainable growth in an increasingly digitised environment. Future implications include the importance of digital education, inclusive technological infrastructure development, and reformulation of social economic law policies to suit the dynamics of the digital era.